Detection and quantification of Staphylococcus in chronic rhinosinusitis. Issue 12 (4th September 2019) - Wagner Mackenzie, Brett; Baker, Jesse; Douglas, Richard G.; Taylor, Michael W.; Biswas, Kristi
Abstract : Background: The sinonasal microbiota has been implicated in chronic rhinosinusitis (CRS) pathogenesis, particularly related to the presence of Staphylococcus aureus . Staphylococcus epidermidis is also prevalent within the sinonasal microbiota and may inhibit S. aureus colonization. We investigated polymerase chain reaction (PCR) primer pairs for measuring absolute abundances of S. aureus and S. epidermidis, then compared bacterial community composition and absolute abundances of these species between CRS patients and controls. Methods: Six candidate Staphylococcus species‐specific primer pairs were tested in silico and in vitro against pure bacterial isolates. Quantitative PCR (qPCR) for absolute quantification of S. aureus, S. epidermidis, and overall bacterial load were assessed in 40 CRS (CRS without nasal polyposis [CRSsNP] = 22, CRS with nasal polyposis [CRSwNP] = 18) patients and 14 controls. Amplicon sequencing of the V3‐V4 hypervariable regions of the 16S ribosomal RNA (rRNA) bacterial gene were conducted to investigate community composition. Results: Primer pairs targeting the gmk gene of S. aureus and nrd gene from S. epidermidis were the most specific and sensitive primers. S. aureus (CRSsNP = 81.8% occurrence, CRSwNP = 83%, control = 92.9%) and S. epidermidis (CRSsNP = 95.5%, CRSwNP = 100%, control = 92.9%) were very prevalent, as indicated by qPCR results. Both CRSsNP and CRSwNP had significantly ( p < 0.05) higher bacterial load when compared with controls ( p < 0.05 for both). No significant correlation was observed between S. aureus and S. epidermidis abundances ( p > 0.05). Conclusion: Bacterial community sequencing detected Staphylococcus ‐assigned sequences in nearly all patients; however, it could not differentiate between S. aureus and S. epidermidis . Here, we present primer pairs that can distinguish between these species. We report a very high prevalence of S. aureus in both CRS patients and controls.